Protective Role of Intracellular Melatonin Against Oxidative Stress and UV Radiation in Saccharomyces cerevisiae - Bisquert, Ricardo; Muñiz-Calvo, Sara; Guillamón, José M. (Frontiers in Microbiology, 2018)
Melatonin (Mel) is considered a potent natural antioxidant molecule given its free-radical scavenging ability. Its origin is traced back to the origin of aerobic life as early defence against oxidative stress and radiation. More complex signalling functions have been attributed to Mel as a result of evolution in different biological kingdoms, which comprise gene expression modulation, enzyme activity and mitochondrial homeostasis regulation processes, among others. Since Mel production has been recently reported in wine yeast, we tested the protective effect of Mel on Saccharomyces cerevisiae (Sc) against oxidative stress and UV light. As the optimal conditions for Sc to synthesise Mel are still unknown, we developed an intracellular Mel-charging method to test its effect against stresses. To assess Mel’s ability to protect Sc from both stresses, we ran growth tests in liquid media and viability assays by colony count after Mel treatment, followed by stress. We also analysed gene expression by qPCR on a selection of genes involved in stress protection in response to Mel treatment under oxidative stress and UV radiation. The viability in the Mel-treated cells after H2O2 stress was up to 35% greater than for the untreated controls, while stress amelioration reached 40% for UVC light (254 nm). Mel-treated cells showed a significant shortened lag phase compared to the control cells under the stress and normal growth conditions. The gene expression analysis showed that Mel significantly modulated gene expression in the unstressed cells in the exponential growth phase, and also during various stress treatments.